The effect of oral administration of monosodium glutamate on orofacial pain response and the estimated number of trigeminal ganglion sensory neurons of male Wistar rats - Ramadhani Amilia; Sofro Zaenal Muttaqien; Partadiredja Ginus (BIO Web of Conferences, 2021)
Monosodium glutamate (MSG) is a worldwide flavor enhancer. The excessive glutamate concentration in nerve tissue induces the death of nerve cells, known as excitotoxicity. In the orofacial region, the nerve cells’ death affects pain perception such as mechanical hyperalgesia and allodynia. The aim of the present study was to examine the pain response modification and the estimated total number of trigeminal ganglion sensory neurons after sub chronic oral administration of MSG. Twenty eight male Wistar rats, aged 6-8 weeks (100-150 grams) were divided into 4 groups: Control (2 mL NaCl 0.9%); 1 mg/gWB MSG; 2 mg/gWB MSG; 4 mg/gWB MSG groups. Daily oral administration of MSG was given for 30 days. The control group received NaCl per oral for the same period. The pin prick and air puff test were performed on days 1-2, days 41-42 and days 55-56. The number of trigeminal ganglion sensory neurons were estimated by the unbiased stereology method, using the approach of numerical density and organ volume reference. The results showed that the sub chronic oral administration of MSG does not modify either the orofacial pain response or the estimated total number of trigeminal ganglion sensory neurons. .